2022
DOI: 10.3390/fermentation8120746
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biofilm Microbiome Formation Developed on Novel 3D-Printed Zeolite Biocarriers during Aerobic and Anaerobic Digestion Processes

Abstract: Background: Aerobic or anaerobic digestion is involved in treating agricultural and municipal waste, and the addition of biocarriers has been proven to improve them further. We synthesized novel biocarriers utilizing zeolites and different inorganic binders and compared their efficiency with commercially available biocarriers in aerobic and anaerobic digestion systems. Methods: We examined BMP and several physicochemical parameters to characterize the efficiency of novel biocarriers on both systems. We also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…According to Figure 15, the microbial community analysis showed an enhanced presence of the Clostridia class in the 3D-printed biocarriers, which have sulfate-reducing capabilities [39] and are known glucose fermenters, generating products critically involved in methane production [40]. Their greater prevalence together with Bacilli compared to K1 ring may indicate that 3D-printed biocarriers are likely to favor the formation of thicker biofilm, composed of anaerobic bacterial groups that are linked to methane production pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Figure 15, the microbial community analysis showed an enhanced presence of the Clostridia class in the 3D-printed biocarriers, which have sulfate-reducing capabilities [39] and are known glucose fermenters, generating products critically involved in methane production [40]. Their greater prevalence together with Bacilli compared to K1 ring may indicate that 3D-printed biocarriers are likely to favor the formation of thicker biofilm, composed of anaerobic bacterial groups that are linked to methane production pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Elliot et al (2017) [13] created spherical biocarriers with a larger specific surface area, something that increased the NH3 removal rate by 1,620 ppm/d compared to common biocarriers. It is worth mentioning that the research of Chioti et al (2022) [15], who studied the efficiency of Kaldnes K1 commercial biocarriers and 3Dprinted biocarriers with 13X and bentonite in aerobic wastewater treatment performed in lab reactors of 150 mL active volume, has also shown a remarkable efficiency in wastewater treatment. According to other researchers [16], the synthetic biofilm carriers showed unstable COD removal rates, in contrast to the natural biofilm carriers that did not present any instability.…”
Section: Introductionmentioning
confidence: 99%
“…The zeolites were mixed with various inorganic composite materials such as bentonite, montmorillonite, or halloysite nanotubes, along with an organic binder, forming a resultant ceramic printing paste. The results revealed that compared to the commercially available carriers, the as-printed carriers exhibited relatively low methane production, high chemical oxygen demand, P (phosphorus), N (nitrogen), NO 2 , and NO 3 reduction, and reduced biofilm formation . In another study, Dong et al designed a fullerene-type nylon-based biocarrier with the help of the SLS 3D printing technique (Figure b).…”
Section: D-printed Modules For Wastewater Treatmentmentioning
confidence: 99%
“…One of the key constituents of bioreactors is the biocarriers which are porous materials that can provide a surface for microorganisms to grow and form biofilms, thereby enhancing the rate of pollutant degradation. 102 The mechanism of action of biocarriers in wastewater treatment involves the attachment of microorganisms to the surface of the carrier, followed by the formation of a biofilm, which provides a protective layer for microorganisms, allowing them to degrade pollutants 103 more efficiently, even under adverse conditions such as high pollutant concentrations, low dissolved oxygen levels, and fluctuations in pH and temperature. Moreover, biocarriers have a density relatively lower than that of water, which allows them to circulate effectively within the bioreactor system.…”
Section: D-printed Modules For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation